2018
DOI: 10.1007/s12020-018-1537-0
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic intra-arterial therapies in metastatic neuroendocrine tumors: lessons from clinical practice

Abstract: Hepatic intra-arterial therapies are well tolerated in the majority of patients with NETs and liver metastases and associated with both clinical improvement and tumor stabilization for prolonged periods. These therapies should be always considered, irrespective of the presence of extrahepatic metastasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 51 publications
0
13
0
1
Order By: Relevance
“…Tumor response is objectivized in 25–86% of cases, and the duration of the response ranges from 6 to 45 months [ 77 79 ]. In a recent series, clinical improvement and tumor response were observed in 95% of patients, with median time to tumor progression of 14 ± 16 months and median overall survival of 22 ± 18 months [ 80 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tumor response is objectivized in 25–86% of cases, and the duration of the response ranges from 6 to 45 months [ 77 79 ]. In a recent series, clinical improvement and tumor response were observed in 95% of patients, with median time to tumor progression of 14 ± 16 months and median overall survival of 22 ± 18 months [ 80 ].…”
Section: Resultsmentioning
confidence: 99%
“…In patients with previous pancreaticoduodenectomy, transarterial therapies are generally contraindicated, due to higher risks of post-procedure morbidity. Liver-directed therapies may also be proposed in patients with extrahepatic metastases to control liver disease and symptoms [ 80 83 ].…”
Section: Resultsmentioning
confidence: 99%
“…Efficacy across modalities appears to be equivalent with imaging and clinical response rates between 60 and 95%. [18][19][20] A multicenter retrospective analysis showed no significant difference in hepatic progression-free survival (PFS) or OS between the different modalities, with median time to progression of approximately 16 months, and outcomes largely determined by liver burden and tumor grade. 21 Comparison between transarterial therapies and indeed across all NET therapies is markedly limited by GEP-NET heterogeneity.…”
Section: Liver-directed Therapymentioning
confidence: 99%
“…Based on these results, the authors suggested that the presence of extrahepatic metastases or unresected primary tumor should not limit the use of TAE and TACE. In another more recent study, clinical response was observed in 95% of the patients treated with various hepatic intra-arterial therapies[ 26 ]. Data about TARE in the treatment of LM from NEN are still limited, but response rates of 70%-90% have been reported[ 27 ].…”
Section: Catheter-based Treatmentsmentioning
confidence: 99%